MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) SISWA KELAS VI SD NEGERI 002 TELUK NILAP KUBU BABUSSALAM - Joeni Asih (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is motivated by the low motivation of student learning in the lesson of Math class VI SD Negeri002 Teluk Nilap Kubu Babussalam. This study aims to improve students' learning motivation in the lesson ofClass VI SD Negeri 002 Teluk Nilap Kubu Babussalam by applying cooperative learning model of teams gamestournament (TGT) type. The subjects of this study are all students of class VI SD Negeri 002 Teluk Nilap KubuBabussalam which amounted to 29 people. The form of research is classroom action research. The instrument ofthis research consisted of performance instrument and data collection instrument in the form of observationsheet of teacher activity and student activity. Based on the results of analysis and discussion can be concludedthat through cooperative learning model type TGT can improve students' learning motivation Math class SDNegeri 002 Teluk Nilap Kubu Babussalam students. Based on the results of the study note that the student'slearning motivation before the action in a classical reach the average percentage of 36.2% is at the interval 0-40%. The first cycle of the first meeting indicates that the students 'level of learning motivation classically onlyreaches the average 51.4% percentage in the 40% -55% interval is quite high and in the second meeting thestudents' learning motivation is classically reaching the percentage average of 56, 9%, are at a 40-55% intervalquite high. While in the first cycle of the first encounter increased with the acquisition of the average valueclassically 71% are at intervals of 56% -75% are high and at the second meeting is klasikal get the averagevalue of 83.4% percentage, is at interval 76- 100% with very high category.